Предмет: Алгебра,
автор: euglovyginae
Помогите пожалуйста!
Приложения:
Ответы
Автор ответа:
1
1,2 (х-3) + 0,4 (1-х) = 4
1,2 х - 3,6 +0,4-0,4х=4
0,8х-3,2 = 4
0,8х = 4 + 3,2
0,8х = 7,2
х = 9
2-3х/4+1-х/2=4-3х/8
2(2-3х)+4(1-х)=4-3х
4-6х + 4-4х = 4-3х
6х + 4-4х = -3х
-10x + 4 = -3x
- 10х + 3х = -4
-7x = -4
х=4/7
1,2 х - 3,6 +0,4-0,4х=4
0,8х-3,2 = 4
0,8х = 4 + 3,2
0,8х = 7,2
х = 9
2-3х/4+1-х/2=4-3х/8
2(2-3х)+4(1-х)=4-3х
4-6х + 4-4х = 4-3х
6х + 4-4х = -3х
-10x + 4 = -3x
- 10х + 3х = -4
-7x = -4
х=4/7
euglovyginae:
Спасибо большое
Похожие вопросы
Предмет: Русский язык,
автор: яхино
Предмет: Русский язык,
автор: zhukovaesya
Предмет: Русский язык,
автор: mintyan
Предмет: Химия,
автор: incorn
Предмет: Химия,
автор: maridyukovskaya